DEVELOPING AUGMENTED REALITY-BASED LEARNING MEDIA ON VOLUME AND SURFACE AREA OF SPACE GEOMETRY FOR STUDENTS GRADE VIII - Medina Rendani Sabana Medina Rendani Sabana (Jurnal Pedagogi Matematika, 2016)
The aim of this research was to develop augmented reality-based learning media on volume and surfaceare of space geometry subject for grade VIII. In particular, the purpose was describing the feasibility of learningmedia in terms of validity, practicality, and effectiveness aspect. This RD (Research and Development) methodused 4D development model, i.e. define, design, development, and dissemination. The last step not carried out dueto time limitations. The subjects of study were VIII-1 and VIII-4 students of SMP N 8 Yogyakarta. The instrumentsused were questionnaires for media experts, material experts, teachers and students to asses the learning media.The questionnaires for expert were based on three quality categories such as goal and content, instructional, andtechnical quality. The results of the assessment of learning media by experts showed that the validity of thelearning media was valid with a score 4.7 from maximum score 5, practically aspect was practical with a score3,23 from maximum score 4, and the effectiveness aspect was effective based on the average score test gained inthe class was more than KKM, that was 80.